Technical Application of Machine-made Sand in the Production of the Commercial Concrete. Issue 1 (January 2021) - Xu, Han; Chen, Xiaobin; Dang, Wei; Guo, Xiujuan; Guan, Jican; Li, Jianrong; Xiong, Qiumin
Abstract: With the lack of natural sand and stone resources, machine-made sand will be widely used in the building materials industry. By adjusting the proportion of machine-made sand and river sand, the application of using the machine-made sand in C30 and C50 concrete was explored. The results indicate that the proportion of machine-made sand is 40% in C30 concrete, which makes the concrete show the best performance and the maximum compressive strength. In C50 concrete, as the proportion of machine-made sand increases, the initial dispersion of concrete gradually decreases, the loss of dispersion increases, and the working performance of concrete decreases. It is worth noting that, regardless of the proportion of machine-made sand, the performance of concrete mixed with machine-made sand is higher than that of concrete prepared with pure river sand at 3d, 7d, and 28d.